Combining methodologies for better targeting of the extreme poor: lessons from BRAC's CFPR/TUP programme (TUP working paper -2) - Matin, Imran; Halder, Shantana R. (BRAC, 2019)
This paper aims to assess the effectiveness and draw lessons from the targeting strategy used in a new BRAC programme called Challenging the Frontiers of Poverty Reduction-Targeting the Ultra Poor (CFPR/TUP) that aims to experiment with a different type of approach to address extreme rural poverty. The underlying theme of both the CFPR/TUP programme and the targeting methodology used is an acknowledgement of the strength of combining different methods and approaches for greater effectiveness. The programme, for instance, combines promotion and · protection oriented mechanisms. Similarly, the targeting approach used in the programme combines various targeting methodologies and knowledge streams about the extreme poor. This paper uses programme data emerging out of its targeting exercise to assess questions of effectiveness of the approach used. Combining the various targeting approaches and drawing from different streams of knowledge has been the main innovativeness of the targeting methodology used in this programme. The large differences we found between the two closely ranked groups of the poor the extreme poor and those just above, also suggest that there is a structural break, rather than a continuum in terms of deprivation of opportunities, security and empowerment that is differentiating the extreme poor from others. It is through a better understanding of the various dimensions, dynamics and interlinkages of these structural breaks that we can design the most effective strategies and programmatic approaches for this group of the poor.